Analysis of sustainability reporting quality and corporate social responsibility on companies listed on the Indonesia stock exchange - Nurzi Sebrina; Salma Taqwa; Mayar Afriyenti; Dovi Septiari (Cogent Business & Management)
This study aims to analyse the diffusion level of non-financial reporting (sustainability reporting, corporate social responsibility, and integrated reporting) in companies listed on the Indonesia Stock Exchange and analyse the quality of sustainable reporting standalone. Indonesia, which is one of the emerging market countries, has not yet established independent sustainable reporting regulations, but a small number of companies in Indonesia are committed to following global regulations to support sustainable development. The study was conducted on public companies listed on the Indonesian stock exchange and examined 240 sustainability reports from 2016 to 2019. For the quality of sustainable reporting standalone, we used the disclosure of triple bottom-line items (economic, environment, social) in accordance with GRI and content analysis to analyze the quality of sustainability reporting based on the GRI (Global Reporting Initiative) principles to measure quality: clarity and accuracy, timeliness, and engagement, stakeholders, comparability, and reliability. This analysis follows, whos argue that in Indonesia public companies, there do not yet require the preparation of a standalone sustainability report. This study shows that the diffusion of sustainability reports is still shallow compared to mandatory social responsibility reports. The quality of sustainability reports based on disclosure is also still low, but industry groups vary in quality. The quality of Sustainability Reporting is based on timeliness and stakeholder engagement, and comparability, satisfactory. However, for clarity and accuracy, the results are acceptable, while reliability is less acceptable.